Oxidation of acetone over Co-based catalysts derived from hierarchical layer hydrotalcite: Influence of Co/Al molar ratios and calcination temperatures. (August 2018) - Zhao, Qian; Ge, Yunli; Fu, Kaixuan; Ji, Na; Song, Chunfeng; Liu, Qingling
Abstract: In order to enhance catalytic performance for acetone, Co-based catalysts prepared under different Co/Al molar ratios and calcination temperatures have been studied in this work. The results indicated that the catalytic activities of the catalysts firstly increased and then decreased with the increase of the Co/Al molar ratio and decreased with the increase of the calcination temperature. Based on the catalytic activities, TG/DTA, XRD, TPR and XPS characterization results, it can be found that catalytic activities of the catalysts with various Co/Al molar ratios were effected by the good crystallization structure of catalyst precursor, surface Co 3+ /Co 2+ molar ratio, low temperature reducibility, and Oads /Olatt molar ratio of the catalysts. Meanwhile, the catalytic activities of the catalysts with different calcination temperatures depended on the low temperature reducibility, surface Co 3+ /Co 2+ molar ratio, porous structure and crystallization structure of the catalyst. Among different synthetic composition, 5:1 CoAlO-300 catalyst (T90% = 225 °C) and 5:1 CoAlO-200 catalyst (T90% = 222 °C) exhibited the efficient acetone oxidation. Highlights: The mechanism of acetone oxidation is related to Co/Al molar ratios and calcination temperatures of the CoAlO catalyst. The reaction temperature (T90% ) decreased by 30 °C over the 5:1 CoAlO-300 catalyst compared to the pure Co3 O4 catalyst. Both Co 3+ and crystallization structure of the CoAlO catalyst are crucial to acetone oxidation over the CoAlO catalyst.